Trends in intensive care unit admissions of COPD patients from 2003 to 2013 in Taiwan - Liao, Kuang-Ming (Int J Chron Obstruct Pulmon Dis, 2018)
OBJECTIVE: The objective of this study was to investigate the trends in COPD patients admitted to the intensive care unit (ICU) in Taiwan from 2003 to 2013. PATIENTS AND METHODS: A retrospective study was conducted to analyze the available data in the National Health Insurance Research Database compiled by the Taiwan Department of Health. We selected patients admitted to the ICU nationwide from 2003 to 2013. Patients older than 40 years with a diagnosis of COPD were enrolled. The ICU admission date was used as the index date. Baseline comorbidities existing before the index date were identified. The comorbidities of interest included diabetes, hypertension, diabetes mellitus, coronary artery disease, stroke, dyslipidemia, cancer, and end-stage renal disease. RESULTS: The number of COPD patients in the ICU increased from 12,384 in 2003 to 13,308 in 2013 (P<0.0001). The mean age of patients and SD was 76.66±9.48 and 78.32±10.59 in 2003 and 2013, respectively. The percentage of COPD patients aged $70 years in the ICU decreased markedly. COPD patients per 10,000 ICU patients decreased for both males and females. The length of ICU stays, and in-hospital mortality increased from 21.58 to 23.14 days and 14.97% to 30.98% from 2003 to 2013, respectively. CONCLUSION: The number of COPD patients admitted to the ICU in Taiwan increased over the 11-year study period. Increased mean patient age, length of ICU stays, hospital mortality, and comorbidities were observed. The use of a nationwide population-based database allowed for a sufficient sample size, generalizability, and statistical power to analyze COPD patients admitted to the ICU in Taiwan.